In His own image and likeness : humanity, divinity, and monotheism - Garr, W. Randall (Culture and history of the ancient Near East, 2003)
This work is about nothing less than Genesis 1, or human creation. Humanity, the author argues, is created within the Priestly tradition as a replacement of God's divine community; human creation marks the decisive moment that God separates himself from other gods and institutes monotheism.